MYCOLOGICAL STUDY IN THE NATURAL-PARK-OF-THE-ALCORNOCALES (ANDALUSIA, SPAIN) .1. AGARICALES - Moreno, G; ESTEVERAVENTOS, F; Ortega, a (CRYPTOGAMIE MYCOLOGIE, 1994)
This work includes the first results about the Agaricales s. lato collected mostly in Quercus suber forest in the Natural Park of the Alcornocales (Andalucia, Spain). The most outstanding taxa are: Hebeloma danicum, H. sacchariolens var. pallidoluctuosum, H. mesophaeum var. pallidum, H. sacchariolens var. pallidoluctuosum, Lactarius luteolus, Pluteus plautus, Russula bresadoliana, R. fragrantissima, R. graveolens var. megacantha, R. graveolens var. purpurata. A microscopical study under the S.E.M. of the spore ornamentation of the most interesting taxa is given.
Keywords: AGARICALES S-LATO; chorology; ecology; taxonomy